Influence of number of daughters per sire on genetic evaluation of Mehsana Buffalo bulls under field progeny testing - Gupta, Jay Prakash; Chaudhari, Jagdish D; Prajapati, Bhavesh M; Srivastva, Amit K; Chauhan, Haresh D; Patel, Praveen A (The Indian Journal of Animal Sciences, 2022)
First lactation production records of 7,825 Mehsana buffaloes, sired by 200 sires maintained at DudhsagarResearch and Development Association, Dudhsagar Dairy, Mehsana over a period of 25 years (1989-2013), wereutilised for estimation of breeding value of the first lactation milk yield using BLUP - Univariate sire model andanimal model using WOMBAT software. The study aimed to find out the optimum number of daughters that maybe sufficient for more accurate and unbiased estimate of breeding value of Mehsana buffalo bulls. The effectivenessof different models run with different daughters per sire for sire evaluation was judged on the basis of within-sirevariance. The maximum and minimum estimated breeding values were 1924.04 l (BLUP-AM, 5 daughters/sire)and 1855.61 l (BLUP-SM, 30 daughters/sire), respectively. However, error variance estimated was highest whenfive daughters/sire were evaluated and lowest, when 30 daughters/sire were evaluated. The present study revealedthat the sire evaluation with sires having minimum 5, 10 and 15 daughters are equally efficient. However, if we doevaluation with sires having daughters more than 20, 25 or 30, additional accuracy of approximately 2.5%, 3% and5%, respectively may be obtained.